APPLICATION OF THE SHANNON ENTROPY AND MULTI-OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS PLUS FULL MULTIPLICATIVE FORM (MULTIMOORA) ON TAEKWONDO BELT INCREASE SELECTION - Norlatifah (Fakultas MIPA Universitas Lambung Mangkurat, 2021)
This research uses the Shannon Entropy method for weighting and the MULTIMOORA method is used for the ranking process. In this study, the selection of belt increases will be carried out by considering several criteria, namely, KIbun Dongjak (Basic Movement), Poomsae, Poomsae Options, Chagi (Kicks), Kyorugi (Fighting), and Theory. Which aims to determine the level of accuracy generated by the two methods. The data used are the selection data for the increase in the taekwondo belt. The result of this study on the application of the Shannon Entropy method and the Multi-Objective Optimization Method On The Basis Of Ratio Analysis Plus Full Multiplicative Form (MULTIMOORA) for Geup 6 with 11 alternative data has an accuracy rate of 76%, for Geup 7 with 12 alternatives the data has an accuracy rate of 65%, for Geup 8 with an alternative number of 13 data has an accuracy rate of 77%, for Geup 9 with an alternative number of 14 data has an accuracy rate of 67%, while for Geup 10 with an alternative number of 6 data has an accuracy level of 86%.